Distribution Pattern And Level Of Exploitation Of Shellfish Species In The Coastal Area Of Gampong Lambadeuk Peukan Bada District Aceh Besar Regency - Nurhaida Nurhaida; M. Ali Sarong; Mimie Saputri; Devi Syafrianti; Asiah M.D (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Mussels belong to the class Bivalvia which has a characteristic in the form of a more or less symmetrical part of the shell. Continuous overexploitation can have an impact on the environment. The purpose of this study was to determine the distribution pattern of mussels, and the level of exploitation of mussels in the Coastal Area of Gampong Lambadeuk, Peukan Bada District, Aceh Besar District.Research data collection was carried out in December 2020.The method used in this research is a survey method with purposive sampling technique.The research location is divided into 3 stations, at each station 3 plots are placed with a size of 1m x 1m.The distribution pattern was analyzed using the Morisita Distribution Index (Id) formula, environmental conditions were analyzed descriptively, and the level of exploitation was analyzed using the FiSAT II program. The results obtained by the distribution pattern at each station,at station I has a clustered distribution pattern (clumped),at station II has a uniform distribution pattern, and at station III it has a uniform distribution pattern. The level of exploitation of shellfish in the study area shows a high level of exploitation with a value of 0.57. The conclusion is that the distribution pattern of shellfish occurs in groups and uniformly, and the level of exploitation is in a high utilization status (over fishing).Keywords: Distribution, Exploitation Rate, Shellfish, Lambadeuk BeachKerang termasuk dalam kelas Bivalvia yang memiliki ciri khas berupa bagian cangkang yang kurang lebih simetris. Tingkat eksploitasi berlebihan secara terus-menerus, dapat mengakibatkan dampak pada lingkungan. Tujuan penelitian ini untuk mengetahui pola distribusi kerang, dan tingkat eksploitasi kerang di Kawasan Pesisir Pantai Gampong Lambadeuk Kecamatan Peukan Bada Kabupaten Aceh Besar. Pengambilan data penelitian dilakukan pada bulan Desember 2020. Metode yang digunakan penelitian ini adalah metode survey dengan teknik purposive sampling. Lokasi penelitian dibagi kedalam 3 stasiun, pada masing-masing stasiun diletakkan 3 plot dengan ukuran 1m x 1m. Pola distribusi dianalisis dengan rumus Indeks Distribusi Morisita (Id), kondisi lingkungan dianalisis secara deskriptif, dan tingkat eksploitasi dianalisis menggunakan program FiSAT II. Hasil penelitian diperoleh Pola Distribusi pada masing-masing stasiun, pada stasiun I memiliki pola penyebaran yang berkelompok (clumped), pada stasiun II memiliki pola penyebaran secara beraturan/seragam (uniform) dan pada stasiun III memiliki pola penyebaran beraturan/seragam (uniform). Tingkat eksploitasi kerang di kawasan penelitian menunjukkan pada tingkat eksploitasi tinggi dengan nilai 0,57. Kesimpulannya adalah pola distribusi kerang terjadi secara berkelompok dan beraturan/seragam, dan tingkat eksploitasi dalam status pemanfaatan tinggi (over fishing).     Kata kunci: distribusi, tingkat eksploitasi, kerang, pantai Lambadeuk